FOREIGN EXPERIENCE OF MULTIMEDIA TEACHING TECHNOLOGIES AND THEIR APPLICATION POSSIBILITIES IN THE CONTEXT OF UZBEKISTAN (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores foreign experiences in the use of multimedia teaching technologies and their potential application in the vocational education system of Uzbekistan. It analyzes successful practices from the United States, Europe, and Asia, including simulation-based training, interactive learning platforms, and digital laboratories. The study highlights how multimedia enhances learner engagement, supports competency-based approaches, and bridges the gap between theory and practice. It further discusses the challenges of implementation in Uzbekistan, including teacher readiness, infrastructure, and the need for localized content. The article concludes that adapting foreign experiences to the Uzbek context can significantly improve the quality of vocational training and align it with international standards.